Efektivitas Model Pembelajaran Creative Problem Solving (CPS) Ditinjau Dari Kemampuan Representasi Matematis Siswa - Destia Ariza Putri; Sri Hastuti Noer (Limacon: Journal of Mathematics Education, 2019)
This research was aimed at finding out the effectiveness of the creative problem-solving learning model which observed from the students’ mathematical representative ability. The population of this research was the students of X MIA at SMA Negeri 14 Bandar Lampung in 2018/2019 academic year which distribute in seven classes. The samples of this research were the students of X MIA 1 and X MIA 2 which was chosen by using cluster random sampling technique. The research design was a randomized pretest-posttest control group design. The data analysis showed the improvement of the mathematic representative ability was not more than 60% from the number of the students who followed the creative problem-solving learning model and improvement of the student's mathematic representative ability that followed the creative problem-solving learning model was higher than escalation of the students who followed conventional learning model. The concluded of this study was the creative problem-solving learning model is not effective which observed from the students’ mathematical representative ability.